A synopsis of Begonia (Begoniaceae) of Southeastern Sulawesi including four new species - Ardi, Wisnu H.; Chikmawati, Tatik; Witono, Joko R.; Thomas, Daniel C. (Phytotaxa, 2018)
Material acquired on a recent expedition to Southeastern Sulawesi, Indonesia, presents an opportunity to reassess and provide an overview of the Begonia flora of the region. Eleven species are recognized including four new species described and illustrated here: Begonia incudiformicarpa, B. iskandariana, and B. tumburanoensis (all in Begonia section Jackia); and B. johntania (Begonia section Petermannia). The former three species are the first confirmed records of section Jackia on Sulawesi substantially extending the known eastern range limit of this section. In addition, an illustration and a lectotypification of Begonia flacca are presented, and an identification key to Begonia species in Southeastern Sulawesi is provided.